Paradoxical Role of BDNF: BDNF(+/−) Retinas Are Protected against Light Damage–Mediated Stress - Wilson, R. Brooks (2007)
PURPOSE: Photoreceptors can be prevented from undergoing apoptosis in response to constant light by the application of exogenous neuroprotective agents, including brain-derived neurotrophic factor (BDNF). BDNF, however, cannot exert its effect directly on photoreceptors because they do not express receptors for BDNF. It has been proposed that BDNF released from Müller cells provides a feed-forward loop, increasing ciliary neurotrophic factor (CNTF) and basic fibroblast growth factor (bFGF) production in Müller cells, which may enhance photoreceptor survival. The authors hypothesized that retinas with reduced BDNF levels in which the BDNF-mediated release of neuroprotective signals is dampened are more susceptible to light-induced photoreceptor degeneration. METHODS: Young adult BDNF(+/+) and BDNF(+/−) littermates (B6.129-BDNF(tm1-LT)) were analyzed. Retinal neurotrophin and growth factor mRNA levels were determined by quantitative RT-PCR, photoreceptor function was assessed through electroretinography, and survival was documented in morphologic sections and in TUNEL assays. Oxidative stress was assayed by measuring glutathione peroxidase activity. RESULTS: baseline, BDNF(+/−) animals had significantly increased levels of glial-derived neurotrophic factor (GDNF) mRNA compared with their wild-type littermates. After light damage GDNF, CNTF, and BDNF mRNA levels dropped 14- to 16-fold in the BDNF(+/+) mice but remained almost unchanged compared with baseline levels in the BDNF(+/−) mice. Preservation of neurotrophin levels in BDNF(+/−) mice correlated with photoreceptor cell survival, preservation of function, and reduced oxidative stress. CONCLUSIONS: Contrary to the hypothesis, reducing BDNF levels resulted in photoreceptor protection against light damage. Survival was paralleled by a reduction in oxidative stress and the preservation of neurotrophin levels, suggesting that chronic reduction of BDNF in the retina provides a level of preconditioning against stress.